State of maxillodental system in children with children's cerebral infantile paralysis - B. N. Mirchuk; T. D. Savitskaya (Kazimierz Wielki University, 2015)
Mirchuk B N, Savitskaya T D. Состояние зубочелюстной системы у детей с детским церебральным параличом = State of maxillodental system in children with children's cerebral infantile paralysis. Journal of Education, Health and Sport. 2015;5(2):149-156. ISSN 2391-8306. DOI: 10.5281/zenodo.15714 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A149-156 https://pbn.nauka.gov.pl/works/541781 http://dx.doi.org/10.5281/zenodo.15714 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015.   УДК  (616.314+616.716.8):616.831-009-053.2/.6Состояние зубочелюстной системы у детей с детским церебральным параличом   State of maxillodental system in children with children's cerebral infantile paralysis   Б. Н. Мирчук, Т. Д. Савицкая B N Mirchuk, T D Savitskaya  Одесский национальный медицинский университет Odessa national medical univercity              Реферат Проведено обследование 114 детей: 102 ребенка с детским церебральным параличом (ДЦП) в возрасте 3-10 лет: 55 детей в возрасте 3-10 лет (молочный прикус), 47 детей в возрасте 6-10 лет (сменный прикус) и 12 практически здоровых детей с физиологическим прикусом. Частота зубочелюстных аномалий у детей с ДЦП в среднем составляет  61,7 %,  из них 52,9 % - аномалии прикуса. У детей с ДЦП установлены высокие показатели интенсивности кариеса молочных и постоянных зубов, воспалительных заболеваний тканей пародонта и плохой уровень гигиены полости рта, а так же задержка минерализации корней постоянных зубов. У детей с ДЦП и аномалиями прикуса повышен тонус жевательных мышц, свидетельствующий о нарушении мышечного равновесия и необходимости использования миофункциональных  ортодонтических аппаратов. Ключевые слова: детский церебральный паралич, зубочелюстные аномалии.               Abstract The inspection of 114 children is carried out: 102 children with children's cerebral paralysis at the age of 3-10 years: 55 children at the age of 3-10 years (milk dentition), 47 children at the age of 6-10 years (mixed dentition) and 12 clinically healthy children with the physiological bite. In children with children's cerebral infantile paralysis the frequency of maxillodental anomalies on the average composes 61, 7 %, from them 52, 9 % composed the anomalies of bite. In children with children's cerebral infantile paralysis are established the high indices of the intensity of caries of milk and permanent teeth, inflammatory diseases of the tissues of periodontium and the poor level of the hygiene of the mouth cavity, and so the delay of the mineralization of the roots of permanent teeth. In children with children's cerebral infantile paralysis and dentoalveolar anomalies is increased the tone of masticatory muscles, which testifies about the disturbance of muscular equilibrium and need of using the myofunctional orthodontic appliances. The purpose of the research. To study the prevalence and intensity of dental caries, incidence of dentoalveolar anomalies, the state of oral hygiene and periodontium children with children's cerebral infantile paralysis. Material and methods. The inspection of 114 children is carried out. The intensity and prevalence of caries teeth, periodontal tissue condition and the delay of the mineralization of the roots of permanent teeth were studied. Conclusions. Analysis of research suggests that children with children's cerebral infantile paralysis frequency dentoalveolar anomalies on average 61,7 %. High caries intensity determined in all age groups. All children surveyed had a poor oral hygiene, which accompanied by inflammation of the periodontal tissues. Assessments of maturity stages of permanent teeth in children with children's cerebral infantile paralysis indicate delay mineralization roots of permanent teeth. Found that children with children's cerebral infantile paralysis and malocclusion increased tone of mastication muscles disclose a violation of muscular balance and the need for myofunctional orthodontic appliances. Key words: cerebral spastic infantile paralysis, dentoalveolar anomalies.